The Role of Business Incubators in Developing Local Digital Startups in Indonesia - Anwar, Muhammad Rehan; Yusup, Muhamad; Millah, Shofiyul; Purnama, Suryari (Startupreneur Business Digital (SABDA Journal), 2022)
The development of the internet causes the flow of information to move quickly without knowing geographical boundaries. Likewise with the development of the digital industry, although the condition of the digital industry in Indonesia is still in its early phase, where infrastructure and ecosystem support is still very minimal, the optimism from digital industry players in Indonesia is very strong, both from the startup side and from investors. Problems arise when investors, both local and foreign, wish to invest in local digital startups in Indonesia, namely the unpreparedness of local startups to receive relatively large amounts of funding for business development. This raises doubts for investors whether startups can manage the funds raised and generate future profits for investors. Therefore, an initiative was born from investors and stakeholders in the digital technology industry to activate business incubators, with the aim of being able to prepare local startups to be able to develop more optimally. The results of this study reveal various tangible benefits received by local startups to increase their capacity.